Application of γ‐cyclodextrin‐lysozyme as host materials for encapsulation of curcumin: characterization, stability, and controlled release properties. (4th June 2022) - Wen, Hedi; Zhang, Deju; Liu, Jingbo; Shang, Xiaomin; Liu, Xuanting; Du, Zhiyang; Zhang, Ting
Abstract: BACKGROUND: In this study, a safe and relatively stable γ ‐cyclodextrin‐lysozyme ( γ ‐CD‐Lys) was synthesized using epichlorohydrin as the cross‐linking agent, and curcumin was successfully encapsulated in γ ‐CD‐Lys. RESULTS: The successful Lys grafting onto γ ‐CD can be demonstrated by a high grafting ratio (79.02%) and was further confirmed by Fourier transform infrared (FTIR) band shifts and the new signal obtained at δ 2.75 in proton nuclear magnetic resonance. The encapsulation efficiency value of γ ‐CD‐Lys was 76.74%, and the successful encapsulation of curcumin into γ ‐CD‐Lys was confirmed by crystal structure change, increased melting point, and FTIR band shifts. The intermolecular bonds results suggested that associative forces between curcumin and γ ‐CD‐Lys were electrostatic interaction, hydrogen bonds interaction, and hydrophobic interaction. The designed nanoparticles had excellent stability at low pH and low salt concentration. The release rate of these nanoparticles was inhibited in simulated gastric conditions, whereas it increased significantly in intestinal media. Simulated gastrointestinal digestion experiments further confirmed that nanoparticles showed higher bioaccessibility (86.05%) compared with curcumin (58.82%). CONCLUSION: Overall, our study showed that the nanoparticles were highly promising for delivering curcumin because of their enhanced functional attributes and stabilization in acid or low salt environments. Also, it was an excellent wall material for targeting hydrophobic bioactive compounds in the intestinal tract via oral administration. © 2022 Society of Chemical Industry.